Информационная грамотность: базовый уровень: электронный курс - Ольгина И. Г. Инна Геннадьевна; Васильев А. В. Артем Викторович; Касымов Д. П. Денис Петрович; Шуберт В. И. Вячеслав Игоревич; Редькина Н. С. Наталья Степановна; Морозова С. А. Светлана Александровна; Пархоменко А. А. Андрей Александрович; Бирюкова Д. А. Дарья Алексеевна; Бахтиярова Е. З. Елена Захаровна; Михайленко В. С. Вера Сергеевна; Фадеев А. С. Александр Сергеевич; Заева Е. А. Елена Анатольевна; et al. (Санкт-Петербург, Stepik, 2024)
Заглавие с экрана